Loss of control over eating, inhibitory control, and reward sensitivity in children and adolescents: a systematic review - Ramalho, Sofia Marlene Marques (2023)
Overview: In recent years, there has been increasing clinical and empirical interest in the concept of pediatric loss of control over eating, particularly about its link with the executive functions related to the concept of impulsivity, such as inhibitory control and reward sensitivity. However, there has yet to be a comprehensive literature synthesis about the associations between these variables. A comprehensive literature synthesis would help identify future research directions to advance the field in this area. Therefore, this systematic review aimed to synthesize evidence concerning the associations between loss of control over eating, inhibitory control, and reward sensitivity in children and adolescents. Methods: The systematic review was conducted according to the guidelines proposed by PRISMA in Web of Science, Scopus, PubMed, and PsycINFO. The Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies was used to assess the risk of bias. Results: Twelve studies met the selection criteria and were included in the final review. Overall, methodological heterogeneity, variability in assessment methods, and the age of participants make it difficult to draw general conclusions. Nevertheless, most studies with community samples of adolescents indicate that inhibitory control difficulties are linked to the concept of loss of control eating. The presence of obesity seems to be associated with inhibitory control difficulties, regardless of the presence of loss of control eating. Studies on reward sensitivity are scarcer. However, it has been suggested that higher reward sensitivity is related to loss of control eating behaviors in young people, particularly binge eating. Conclusions: The literature on the link between loss of control eating and trait-level facets of impulsivity (low inhibitory control and higher reward sensitivity) among young people remains limited, and more studies on children are needed. Findings from this review may make healthcare professionals more aware of the potential clinical importance of targeting the trait-level facets of impulsivity and help to inform existing and future weight-loss/maintenance interventions in childhood and adolescence.